Accounting Standards Reporting in Digital Technologies Exploring Benefits Challenges and Potential Risks - Abalaka James Nda; Lukman Ojedele Lawal; Sulaiman Taiwo Hassan (International Journal of Science and Society (IJSS), 2025)
In today’s era of the Fourth Industrial Revolution, digital technologies have become essential in the field of accounting. These technological advancements are reshaping all business sectors, including accounting, with both positive and negative consequences. The rapid adoption of digital tools is challenging accounting professionals and recent graduates to acquire new digital competencies. However, despite the growing presence of these technologies, there remains a gap in understanding their overall impact on accounting practices. This study provides a critical analysis of the role digital technologies play in accounting and reporting, emphasizing their benefits, limitations, and associated risks. Employing a systematic literature review alongside an inductive approach and thematic analysis, the research reveals that, although issues such as inadequate data governance, cybersecurity threats, and privacy concerns persist, digital technologies significantly enhance accounting by enabling real-time data access, automating routine tasks, facilitating data visualization, supporting big data analytics, reducing errors, and improving operational efficiency. Ultimately, these technologies are revolutionizing accounting processes by increasing both effectiveness and productivity. The study advocates for accounting professionals, practitioners, and policymakers to prioritize investment in emerging digital innovations.